Pengaruh Financial Literacy dan Self Control Terhadap Financial Management Behavior pada Gen Z - Nithaqaini Yurasti, Inggih Asma; Buchdadi, Agung Dharmawan; Iranto, Dicky (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to determine the effect of financial literacy, self-control on financial management behavior in Gen Z. This study uses a quantitative method with primary data sources using questionnaires distributed online. The research sample uses a purposive sampling technique with the criteria of Gen Z samples, domiciled in JABODETABEK, and have used Shopee. The number of samples collected was 251 respondents processed using the SEM PLS research model. And using the Theory of Planned Behavior. The results of this study indicate that the hypothesis test of financial literacy on financial management behavior has a positive and significant relationship, self-control has a positive and significant effect on financial management behavior, financial literacy has a positive and significant relationship with self-control. In addition, self-control as a mediating variable is able to influence the relationship between financial literacy and financial management behavior. The practical implications of this study are expected that Gen Z can continue to increase or secure awareness of the importance of financial literacy and build and be able to control themselves not to shop excessively so that they have the ability to manage their finances.